Dampak Kebijakan Proteksi terhadap Ekonomi Gula Indonesia - Prajogo Utomo Hadi; Sri Nuryanti (Jurnal Agro Ekonomi, 2005)
EnglishSince the agreements on agriculture under the WTO arrangements came into  effect by 1 January 1995, the Indonesian sugar economy has been increasingly squeezed. This was due to excessive quantity of sugar imports, especially since the economic crisis in 1997. The decreased world prices have affected the domestic prices that brought about the national sugar industry increasingly less competitive. To deal with this crucial problem, the Indonesian government launched protection policies, including tariff and nontariff measures. In 2003, the tariff rates were Rp 550/kg for raw sugar and Rp 700/kg for white sugar. Meanwhile, the nontariff measure involved import arrangement, control and restriction. In relation to this problem, the objective of the research was to estimate the effects of the tariff and nontariff policies on the national sugar economy both at the aggregate and farm levels. Using a partial equilibrium model, this research found that the protection policies have significantly reduced import quantity and at the same time significantly increased the domestic prices, domestic production, producer’s surplus and farmer’s income. Elimination of one or both policies would bring back the national sugar industry into bankruptcy. It is suggested, therefore, that: (1) The Indonesian government needs to retain the existing protection policies; (2) Indonesia together with other countries has to make more pressures on developed countries so as to reduce their export subsidies and domestic supports that would improve world prices; and (3) Always attempting improvement in sugar cane farming and sugar processing factory to improve competitiveness. IndonesianSejak diberlakukannya perjanjian pertanian WTO tanggal 1 Januari 1995, perekonomian gula Indonesia makin terpuruk karena membanjirnya impor, terutama sejak krisis  ekonomi 1997. Harga dunia yang terlalu rendah telah mengimbas ke pasar dalam negeri sehingga industri gula nasional makin tidak kompetitif. Menghadapi masalah ini, pemerintah Indonesia kemudian menempuh kebijakan proteksi, yang terdiri dari kebijakan tarif dan nontarif. Pada tahun 2003, tingkat tarif impor adalah Rp 550/kg untuk gula mentah dan Rp 700/kg untuk gula putih, sedangkan kebijakan nontarif adalah pengaturan, pengawasan dan pembatasan impor. Sehubungan dengan itu, tujuan tulisan ini adalah mengestimasi dampak kebijakan tarif dan nontarif terhadap perekonomian gula nasional di tingkat makro agregat dan tingkat mikro usahatani. Dengan menggunakan pendekatan model keseimbangan parsial, penelitian ini menyimpulkan bahwa kebijakan proteksi telah berhasil secara signifikan menurunkan impor dan meningkatkan harga gula dalam negeri, produksi, surplus produsen dan pendapatan petani. Penghapusan salah satu kebijakan tersebut, apalagi keduanya, akan menyebabkan  industri gula nasional terpuruk kembali. Oleh karena itu disarankan agar: (1) Pemerintah tetap mempertahan-kan kebijakan proteksi yang ada; (2) Terus berjuang bersama dengan negara-negara lain untuk menekan negara-negara maju agar mau menurunkan subsidi ekspor dan bantuan domestik sehingga harga gula dunia meningkat; dan (3) Terus mengupayakan perbaikan efisiensi usahatani tebu dan pabrik gula untuk meningkatkan daya saing.